2011
DOI: 10.1016/j.jaac.2011.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Onset Patterns in Autism: Correspondence Between Home Video and Parent Report

Abstract: Objective The onset of autism is usually conceptualized as occurring in one of two patterns, an early onset and a regressive pattern. This study examined the number and shape of trajectories of symptom onset evident in coded home movies of children with autism and examined their correspondence with parent report of onset. Methods Four social-communicative behaviors were coded from the home video of children with autism (n = 52) or typical development (n = 23). All home video from 6 through 24 months of age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 34 publications
1
91
0
4
Order By: Relevance
“…Recent papers have pointed out significant complexities in defining and measuring the onset of autism symptoms (18). Studies have demonstrated relatively low correspondence between parent report of onset and home videotape evidence of symptom trajectories (26), with one study showing that 45% of participants clearly demonstrated a regression on videotape that was not reported by parents (27). Similarly, a recent prospective study found that regression was evident in many infants who were developing autism but was reported by only a minority of parents (28).…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers have pointed out significant complexities in defining and measuring the onset of autism symptoms (18). Studies have demonstrated relatively low correspondence between parent report of onset and home videotape evidence of symptom trajectories (26), with one study showing that 45% of participants clearly demonstrated a regression on videotape that was not reported by parents (27). Similarly, a recent prospective study found that regression was evident in many infants who were developing autism but was reported by only a minority of parents (28).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is not clear when and how the behavioral symptoms begin to emerge. Symptoms may emerge after a period of relatively typical development either as a result of a loss of skills 16 or a failure to acquire new skills 17, 18 . The conceptualization of onset patterns is further complicated by the finding that some symptoms may show a gradual decrease in frequency (e.g., eye contact), whereas others fail to increase at the rate observed in typical controls 19 (e.g., social vocalizations), suggesting that the departure from typical trajectories in specific domains may follow different patterns and take place during different developmental periods.…”
Section: Introductionmentioning
confidence: 99%
“…8 Second, a proportion of children with ASD reportedly regress in the second year. Recent research has indicated only modest agreement between retroactively reported regression and analysis of behavioral change as observed on serial home videos 9 and that acute skill loss may exist along a continuum of gradually declining trajectories of social and communicative behavior. 10,11 However, interventions during this period may counter the developmental cascade that contributes to progressive symptom development and ultimately prevent ASD-related impairments before they fully manifest.…”
mentioning
confidence: 99%